A feasibility study on bamboo – PLA composite lamina using the mechanics of composite materials - B. Vishwash; K.B. Sachidananda; N.D. Shivakumar (Advances in Bamboo Science)
This paper examines the implications of fibre angle and its volume fraction (Vf) on the engineering constants of composite lamina reinforced with bamboo fibres (BFs). A polylactic acid (PLA) matrix reinforced with BFs was used to assess the engineering performance constants. The response of bamboo-PLA (BF-PLA) green composite lamina for different Vf was also included in this study. Using the mechanics of composite lamina, the engineering constants of the lamina were varied for fibre orientation angles ranging from 0° to 90° and for Vf ranging from 0.1 to 0.5 in increments of 0.1 (10 %). Additionally, for fibre orientation of 0° and Vf between 0 % (full matrix) and 100 % (full fibres), the investigation provided a range in the lamina's longitudinal tensile strength in increments of 0.01 (1 %). To learn more about the BF-PLA lamina and whether it was feasible to proceed with an experimental investigation, the results were plotted for a comparative analysis. We demonstrated that the bamboo Vf and orientation significantly affect the lamina's longitudinal tensile strength in addition to its engineering constants. We found that there was a critical fibre volume percentage of 8.2 % and a minimal fibre volume fraction of 7.3 %. We discuss the BF-PLA lamina and the applicability in designing facesheets for sandwich composite construction. Considering the outcomes of the macromechanical and micromechanical analysis of lamina, we conclude that the BF-PLA composite has the potential to act as biodegradable facesheets for environmentally friendly sandwich structures. This needs to be further explored by experimental and finite element studies.